2017
DOI: 10.1142/s0219493718500107
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior, attracting and quasi-invariant sets for impulsive neutral SPFDE driven by Lévy noise

Abstract: By establishing two new impulsive-integral inequalities, the attracting and quasi-invariant sets of the mild solution for impulsive neutral stochastic partial functional differential equations driven by Lévy noise are obtained, respectively. Moreover, we shall derive some sufficient conditions to ensure stability of this mild solution in the sense of both moment exponential stability and almost surely exponential stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…If Ψ Q < ∞, then Ψ is known as Q-Hilbert Schmidt operator. For more details on concepts and theory on SDEs, one can refer to the articles [1,4,9,13,21] and references therein.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…If Ψ Q < ∞, then Ψ is known as Q-Hilbert Schmidt operator. For more details on concepts and theory on SDEs, one can refer to the articles [1,4,9,13,21] and references therein.…”
Section: Preliminariesmentioning
confidence: 99%
“…Li [17] discussed the global attracting set and quasi-invariant set of impulsive neutral stochastic functional partial differential equations driven by fractional Brownian motion (fBm). In very recent years, a few works have been done on the qualitative properties of solutions for attracting set and quasi-invariant set of SDEs system, readers are referred to [6,10,13,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lakhel et al [33] showed the existence, uniqueness, and asymptotic behavior of mild solutions for a family of neutral functional stochastic differential equations with fBm and Poisson jumps. Huan and Agarwal [25] found attractive and quasi-invariant sets of the mild solution for impulsive neutral stochastic PDEs driven by Levy noise. Sakthivel and Ren [56], addressed the complete controllability of stochastic evolution equations with jumps in a separable Hilbert space, while in, Ren et al [53] studied the approximate controllability of stochastic differential systems driven by Teugels martingales coupled with a Levy process.…”
Section: Introductionmentioning
confidence: 99%